REMOTE EXPERIMENTS WITH SIMPLE TECHNICAL DEVICES - LUSTIG, Frantisek (Trends in education, 2013)
Remote experiments are new objects in the teaching of natural sciences. They are created with the universal measuring systems (ISES, LabVIEW, etc.). The paper presents examples of remote experiments with simple standard laboratory instruments (laboratory power supplies, multimeters, etc.) with interface RS232C or USB. Remote experiments are easy to use on those instruments and special modular software ISES WEB Control.
Keywords: measuring system ISES; ISES WEB Control software; laboratory instruments; RS232C.